Culture-positive Pediatric Tuberculosis in Toronto, Ontario: Sources of Infection and Relationship of Birthplace and Mycobacterial Lineage to Phenotype. Issue 1 (January 2016) - Rayment, Jonathan H.; Guthrie, Jennifer L.; Lam, Karen; Whelan, Michael; Lee, Brenda; Jamieson, Frances B.; Kitai, Ian
Abstract : Background: Few data relate Mycobacterium tuberculosis ( Mtb ) lineage and disease phenotype in the pediatric population or examine the contribution of travel to the tuberculosis (TB)-endemic country in North America. We examined clinical, demographic and Mtb genotype data from patients with TB who were treated in Toronto between 2002 and 2012. Methods: Consecutive Mtb culture-positive, pediatric patients were included. Clinical data were collected from a prospectively populated clinical database. Mtb case isolate genotypes were identified using Mycobacterial Interspersed Repetitive Units–Variable Number Tandem Repeat (MIRU-VNTR) and spoligotyping and were categorized into phylogeographic lineages for analysis. Results: The 77 patients included 30.4% of all culture-positive pediatric TB cases in Ontario from 2002 to 2012. Seventy-six (99%) patients were first or second generation Canadians. Foreign-born patients were more likely to have extrathoracic disease [odds ratios (OR) = 3.0; 95% confidence interval (CI): 1.04–8.71; P < 0.05] and less likely to have a genotype match in the Public Health Ontario Laboratories database [OR = 0.32 (95% CI: 0.11–0.90); P < 0.05] than Canadian-born patients. For those without a known TB contact, Canadian-born patients were more likely to have travelled to a TB-endemic country [OR = 13.0 (95% CI: 2.5–78.5); P < 0.001]. Extrathoracic disease was less likely in patients infected with the East Asian Mtb lineage [OR = 0.1 (95% CI: 0.01–0.9); P < 0.05] and more likely in those infected with the Indo-Oceanic Mtb lineage [OR = 5.4 (95% CI: 1.5–19.2); P < 0.05]. Conclusions: Travel to TB-endemic countries likely plays an important part in the etiology of pediatric TB infection and disease, especially in Canadian-born children. Mtb lineage seems to contribute to disease phenotype in children as it has been described in adults. Abstract : Supplemental Digital Content is available in the text.